An Unusual Case of Bilateral Bronchiectasis Following Foreign Body Aspiration (Chest & Heart Journal, 2023)
Foreign body (FB) aspiration can be fatal if it obstructs the glottal opening, larynx, or trachea. Delayed presentations usually occur when the foreign matter obstructs one of the principal or distal bronchi and results in recurrent pneumonia, bronchiectasis, lung abscess or pyopneumothorax. FB aspiration is more common in younger children below the age of three years but not uncommon in older children and young adults.It is an uncommon cause of bronchiectasis. Here, we present a case of a 12 years boy who suffered an incidence of FB aspiration seven months back and presented with bilateral bronchiectasis and pneumonia. Development of bilateral bronchiectasis due to a single airway foreign body is very unusual. Nevertheless, this patient was revealed to have bilateral bronchiectasis along with consolidation.Chest Heart J. 2021; 45(2) : 99-102